The Historiai of John Tzetzes: a Byzantine 'Book of Memory'?. (18th September 2017) - Pizzone, Aglae
Abstract : The paper provides for the first time a full-fledged analysis of the structure and compositional principles sustaining John Tzetzes' Chiliades or Historiai . The article is divided into three sections. The first focuses on the developments of commentary literature in late twelfth-century Byzantium, showing how exegesis is used to textualize the authorial self and create autobiographical narratives. The second delves into the purpose of the work and its audience. The final section, focusing on the first part of the work, explores the role of memory in the Historiai and in particular, the interplay between cultural memories and experience in Tzetzes' self-presentation.